Створення міждисциплінарних навчальних проектів stem освіти з використанням мови програмування python - Скиданенко, Я. С.; Стрілкова, Т. О. (ХНУРЕ, 2025)
Modern STEM education necessitates the integration of interdisciplinary methodologies that enable students to explore complex scientific phenomena through computational modeling and programming. This paper presents an educational approach based on Python for analyzing nanostructures using stochastic methods. The study provides a comparative analysis of stochastic and deterministic modeling approaches, highlighting the advantages of Monte Carlo methods and stochastic differential equations in capturing nanoscale absorption dynamics.
Keywords: міждисциплінарний навчальний проект; STEM education